The Effect of Decreasing Temperature on Arthropod Diversity and Abundance in Horse Dung Decomposition Communities of Southeastern Massachusetts - Patrick Kearns; Robert D. Stevenson (Psyche: A Journal of Entomology)
Dung from large mammalian herbivores provides a concentrated food resource, rich in bacteria, nitrogen, and many forms of carbon that support a diverse community of arthropods. Detrital communities, while essential to nutrient cycling, are poorly studied. From July 2010 to October 2010, we sampled these arthropod assemblages using pitfall traps baited with horse dung at five sites southeast of Boston, MA. A total of 396 samples were collected, resulting in 10,299 arthropod specimens. We found a highly diverse group of arthropods dominated by Coleoptera (n=3696) and Diptera (n=3791) and noted the absence of hymenopterans, a group that was dominant in previous studies on these communities. The community had a high level of evenness (0.93 Shannon evenness) and lacked a dominant species, with no one species obtaining more than 7% relative abundance. Species accumulation curves indicate near maximum diversity was reached for each site and the study as a whole (93% maximum calculated Shannon Diversity). A strong effect of seasonality was also observed on the community, as shown by a strong shift in community at the end of August. The community sampled displayed a high similarity to previous studies, indicating a cosmopolitan distribution as well as an opportunistic community.